(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3CNHQfG gGTe Hf eMeO GdNRGYj ONd CYQGHj ef Hfj Sdje hcGf jSei CHGGdbfGaP adeG eKd Hjf jOjg CfTOg(B: (3eQGV GdYjhf NeGU GdHWhf WhGd GdeJhf hUGQ GdNWG s
(3BNQgG (B:s
(3dG JNGdj Cfj fSjJc deG MGd rHjTQ he Hg Nda XgQj bGd EHQGgje(B: (3ahbaJ Ydi bHQg Edi LfH bHQgG ced GdSaQ GdQGHY ef cJGH GdLGeY GdcHjQ aj GdCZGfj s
(3ef fSNI QGHYIs
(3HChdg agQSJ HGdCNHGQ GdhGQOI ajgs
(3hQO CjVkG JMJ Qbe (B2176s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs